Contents in the television of Ecuador. Incidence of the digital transition and the regulation - Suing Ruiz, A. (2016)
In the television of Ecuador a commercial model has predominated. It has not allowed the production of national content, situation that in recent years has changed thanks to the transition to Terrestrial Digital Television and the implementation of the Communications Law that promotes, both technically and legally, the domestic production to meet the demand for quality content. In addition, the digital phenomenon and the regulation in communication would allow to meet the right to communication. The research presents the changes in the composition of content of private television of Ecuador between 2010 and 2015; and the findings of media actors. The effectiveness and exploitation of technological and legal changes will depend on the ability of agreements between companies, society and the government.